Job Safety Analysis dan Rencana Anggaran Biaya Dalam Rangka Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja di PT. Tebo Agung International, Kabupaten Tebo, Provinsi Jambi - Arif Setiawan; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT. Tebo Agung International is one of the private companies engaged in coal mining. This company is located in Semambu Village, Sumay District, Tebo Regency, Jambi Province. At the beginning of November 2018, PT. Tebo Agung International plans to conduct mining operations. At present the company is still in the preparation stage in implementing Occupational Safety and Health Management System as the construction and exploitation process progresses. To fulfill the regulations in implementing Occupational Safety and Health Management System, making Job Safety Analysis and Occupational Health and Safety economic studies needs to be done to find out the Budget Plan that will be issued by the company. Based on the results of the discussion, the conclusions about the potential hazards in the construction process the most risk is that the head is crushed by material from the rising work. In the process of exploitation, a potential danger that often occurs is falling while doing P2H and the most risk is a collision with a compressing unit that allows the victim to properly damage the unit. Then, the value of the occupational safety and health budget plan for implementing the Occupational Safety and Health Management System is Rp. 179.017.000. Keywords: Job Safety Analysis, Budget Plan, Occupational Safety and Health Management System, Personal Protective Equipment